Інтеграція збутових технологій в діяльності підприємств сфери торгівлі та їх логістично-мережевого розвитку - Кравченко, М.С.; Кузьм’як, Ю.Й.; Тарасов, В.Г. (Економічний вісник Донбасу, 2023)
Інтеграційні процеси є позитивним потенціалом стійкості та сталого розвитку суб’єктів морської торгівлі. В статті проаналізовано динаміку світового індексу контейнерів Drewry та пропускної здатності контейнерів і вантажопрохідності в контейнерному порту в Шанхаї, де виявлено, що зниження попиту на морські перевезення дали змогу подолати величезні відставання роботи та скорочення часу очікування в портах та забезпечити доходну складову, пов’язану із кризовими економічними процесами.
Досліджено найкращі контейнерні лінії світу протягом 2020-2022 років з виокремленням їх особливостей розвитку та проаналізовано потенціал найбільших десяти контейнерних ліній світу на період ІІІ кварталу 2023 року, де визначено, що не всі компанії мають позитивні зрушення свого розвитку, утримуючи лідируючі позиції у відповідному рейтингу.
Розглянуто можливості розвитку суб’єктів інтеграційних процесів морської торгівлі, зосереджуючись на Maersk, як прикладу вертикальної інтеграції контейнерної логістики та Hong Kong Seaport Alliance – горизонтальної, де представлено головні їх стратегічні напрямки діяльності на умовах сталості. За результатами проведених досліджень запропоновано шляхи сприяння подальшого сталого розвитку морської торгівлі на умовах розширення та удосконалення техніко-технологічного оснащення та впливу урядів країн для прискорення відповідного процесу. Integration processes have positive potential for the stability and sustainable development of maritime trade entities. The integration processes of the maritime industry expand the opportunities of the subjects of their activities, creating conditions of market stability and the potential for development, taking into account modern trends. Each direction of the integration process has its own risks and advantages, but the orientation of companies towards a single goal of sustainable development, joining efforts in the direction of maximum satisfaction of customer needs, and obtaining a positive financial effect is the main advantage in solving issues of any level of complexity. The corresponding development is aimed at a technical and technological breakthrough in the maritime industry, which opens the way to reducing costs while obtaining the maximum results.
This study analyzes the dynamics of the Drewry World Container Index, container throughput, and cargo throughput at the Shanghai Container Port, where it was found that the decrease in demand for sea transportation has made it possible to overcome huge backlogs, reduce waiting times in ports, and provide a revenue component related to economic crises. The world's best container lines from to 2020-2022 were studied, highlighting their development features, and the potential of the world's ten largest container lines for the period of the third quarter of 2023 was analyzed. It was determined that not all companies have positive changes in their development, maintaining leading positions in the corresponding rating. The possibilities of developing subjects for the integration processes of maritime trade are considered, focusing on Maersk as an example of vertical integration of container logistics and the Hong Kong Seaport Alliance – horizontal integration, where their main strategic directions of activity under sustainability conditions are presented. Based on the results of the research, ways of promoting further sustainable development of maritime trade are proposed under the conditions of expansion and improvement of technical and technological equipment and the influence of the governments of countries to accelerate the relevant process.